2009
DOI: 10.1007/s11430-009-0130-z
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of mafic enclaves from the north Taihang Yanshanian intermediate to felsic plutons: Evidence from petrological, geochemical, and zircon Hf-O isotopic data

Abstract: We report the zircon Hf-O isotopic data for mafic enclaves from the Taihang Yanshanian intermediate to felsic plutons, and use them, along with the petrological, whole-rock chemical and Nd-Sr isotopic data, to reveal the petrogenesis of mafic enclaves. Mafic enclaves show magmatic textures and are finer-grained than host rocks. In places they are highly elongated due to stretching within the partially crystallized, convective felsic magma, but show no solid-state deformation. These data suggest that mafic encl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…xenoliths (usually country rocks; e.g., , refractory and residual phase assemblages derived from granitoid sources (e.g., the restite model; Chappell et al, 1987;Chappell and White, 1991), chilled material or cumulate of early-formed co-genetic crystals (e.g., Dodge and Kistler, 1990;Dahlquist, 2002;Donaire et al, 2005;Chen et al, 2015), and basaltic melt material incompletely digested and homogenized during a magma mixing process (e.g., Didier, 1987;Castro et al, 1990;Dorais et al, 1990;Chappell and White, 1991;Chen et al, 2009aChen et al, , 2013b.…”
Section: Petrogenesis Of the Mafic Magmatic Enclavesmentioning
confidence: 99%
See 1 more Smart Citation
“…xenoliths (usually country rocks; e.g., , refractory and residual phase assemblages derived from granitoid sources (e.g., the restite model; Chappell et al, 1987;Chappell and White, 1991), chilled material or cumulate of early-formed co-genetic crystals (e.g., Dodge and Kistler, 1990;Dahlquist, 2002;Donaire et al, 2005;Chen et al, 2015), and basaltic melt material incompletely digested and homogenized during a magma mixing process (e.g., Didier, 1987;Castro et al, 1990;Dorais et al, 1990;Chappell and White, 1991;Chen et al, 2009aChen et al, , 2013b.…”
Section: Petrogenesis Of the Mafic Magmatic Enclavesmentioning
confidence: 99%
“…Actually, there are many compelling lines of evidence for magma mixing in many granitoids, especially (1) where a clear isotopic contrast exists between the MMEs and the hosts (e.g., Chen et al, 2009b;; and (or) (2) where disequilibrium features occur in the MMEs, e.g., complex zoning of clinopyroxene crystals that have distinctly low-MgO cores surrounded by high-MgO rims (e.g., Chen et al, 2013a;, or resorption textures or reversed zoning of plagioclase Chen et al, 2009aChen et al, , 2009b). In the case of our study, however, none of the above has been observed.…”
Section: Page Of 40mentioning
confidence: 99%
“…MMEs are commonly observed in the granitoid intrusions, and have been used to determine the genesis of the granitoid intrusions and their tectonic setting (Chen et al, 2009;Duan et al, 2015;Sun et al, 2016;Zheng et al, 2016;Sun et al, 2017). Previous research proposed that MMEs could be possible products of several magmatic processes: (1) restite after partial melting in the source region (White et al, 1999;Sun et al, 2016); (2) the xenoliths of the earlier magmatic cumulates (Clements et al, 1986); (3) wall rocks xenoliths from the emplacement of the granodiorite (Zhou et al, 1994); and (4) magma mixing (Janousek et al, 2004;Kumar et al, 2004;Kemp et al, 2004;Chen B et al, 2013).…”
Section: The Genesis Of Host Granodiorite and Its Mmes 521 Origin Of The Mmesmentioning
confidence: 99%